Tribological performance of DLC/DLC and steel/DLC contacts in the presence of additivated oil - Mannan, Abdul; Sabri, Mohd Faizul Mohd; Kalam, Md. Abul; Masjuki, Haji Hassan (Inderscience, 2018)
In this study, the tribological properties of ta-C DLC were largely influenced by the counter surfaces and additives. The DLC/DLC contact showed approximately 60% lower wear when tested with additivated oil compared to that of base oil and this result was 66% in steel/DLC contact. Friction coefficient in DLC/DLC contact was lower than in steel/DLC contact under both oils. But however, both contacts showed slightly higher friction coefficient under additivated oil compared to that of base oil. In steel/DLC, the thermo-chemical reaction between carbon and iron and/or the fusion of the transferred particles were prevented by additives which were present under base oil. The fracture found on DLC surface in steel/DLC contact under additivated oil indicates that the tribolayer formed on the steel surface would be of brittle nature. The passivation of surfaces in DLC/DLC contact by additives prevented the damage which was observed under base oil.